Overweight Adolescents and Life Events in Childhood - Lumeng, Julie C. (Pediatrics, 2013)
OBJECTIVES: To test the association of life events in childhood with overweight risk in adolescence; to examine the effects of chronicity, timing, intensity, valence, and type of life events; and to test potential moderators. METHODS: Mothers of children enrolled in the Eunice Kennedy Shriver National Institute of Child Health and Human Development Study of Early Child Care and Youth Development responded to the Life Experiences Survey at ages 4, 9, and 11 years. Using logistic regression analysis, we tested the association of experiencing many negative life events with being overweight at age 15 years, controlling for child gender, race/ethnicity, maternal education, and maternal obesity. Child gender, maternal education, maternal obesity, child’s ability to delay gratification for food, and maternal sensitivity were tested as moderators. RESULTS: Among the 848 study children (82% non-Hispanic white), experiencing many negative life events was associated with a higher risk of overweight (odds ratio: 1.47 [95% confidence interval: 1.04–2.10]). Greater chronicity and negative valence of the event were associated with greater overweight risk; timing of exposure and maternal reported impact of the event were not. The association was more robust for events related to family physical or mental health and among children of obese mothers and children who waited longer for food. CONCLUSIONS: Children who experience many negative life events are at higher risk of being overweight by age 15 years. Future work should investigate mechanisms involved in this association, particularly those connected to appetitive drive and self-regulation; these mechanisms may hold promise for obesity prevention strategies.